2017
DOI: 10.4081/jae.2017.612
|View full text |Cite
|
Sign up to set email alerts
|

Vineyard pruning residues pellets for use in domestic appliances: a quality assessment according to the EN ISO 17225

Abstract: Nowadays many types of biomass are studied to satisfy the increased demand of renewable energy based on pellet combustion. However, only a few biomasses fulfil the high quality standard required for pellet used in domestic appliances. European and International standards in force define this quality of non-industrial use of pellets in term of the origin of biomass, physical, mechanical and chemical parameters. Vineyard residues are a worldwide potential source of energy but their compliance to be used in domes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
(65 reference statements)
2
21
1
Order By: Relevance
“…Most chemical parameters analyzed in laboratory for pruning and pellet are comparable with the results found in previous studies [30][31][32]. The main variations refer to heavy metals, due to the different harvesting systems and storage conditions.…”
Section: Discussionsupporting
confidence: 84%
“…Most chemical parameters analyzed in laboratory for pruning and pellet are comparable with the results found in previous studies [30][31][32]. The main variations refer to heavy metals, due to the different harvesting systems and storage conditions.…”
Section: Discussionsupporting
confidence: 84%
“…Additional savings are possible by using vine wood pellet produced in the farm from pruning residuals. Vineyards can produce 1 to 2.5 t of dried vineyard residual per hectare [20], so that flaming for weed control would use just a portion of it. However, while harvesting of pruning residuals is a well-established technique [21], further research is still needed to optimize biomass processing and vine wood pellet production [22].…”
Section: Biomass Flaming: Still Open Issues and Further Perspectivesmentioning
confidence: 99%
“…Picchi et al [21] demonstrated the excellent performances of electrostatic filters to reduce total fly ash emissions of boilers specifically tailored for biomass with high content of ash. Also Zanetti et al [19], Pizzi et al [20] and Picchi et al [21] demonstrate the lower costs of woodchips compared to pellets in spite of the slightly lower performances in terms of combustion efficiency and emissions of pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the base case, the proposed alternative uses lead to the reduction (from 1.6 to 9.5 times) of the environmental impact indicators belonging the categories of climate change, ozone depletion, acidification and freshwater eutrophication but an increase (up to 38 times) of the indicator categories strongly related to the wood combustion, such as particulate matter and photochemical oxidant emissions. Zanetti et al [19] analyzed the properties of different shapes of vine biomass and their behavior during combustion in domestic stoves and industrial boilers, demonstrating that the former cannot comply with the EN ISO 17225 International Standards. Pizzi et al [20] tested vine pruning pellets in a 150 kW boiler, measuring the total suspended particles (TSP), CO and NO X emissions.…”
Section: Introductionmentioning
confidence: 99%